2010
DOI: 10.1063/1.3372757
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructuring in Ge by self-ion implantation

Abstract: We report here a detailed study about the formation and self-organization of nanoscale structures during ion beam implantation at room temperature of 300 keV Ge+ in Ge as a function of the ion fluence in the range between 1×1014 to 4×1016 cm−2. “Microexplosions” characterize the morphology of the swelled material; a random cellular structure consisting of cells surrounded by amorphous Ge ripples has been observed and studied in details by combining atomic force microscopy, scanning electron microscopy, and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
70
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 19 publications
6
70
0
1
Order By: Relevance
“…An Figure 1 reports SEM images depicting the surface of the two samples implanted with 5x10 15 at/cm 2 fluence at room and liquid nitrogen temperature, respectively. It is evident that nano-voids formed under Sn + irradiation as expected from literature for high fluencies and high mass ion bombardment [10,11]. The voids are distributed on the sample surface with the typical 'honeycomb' symmetry.…”
Section: Methodssupporting
confidence: 56%
See 1 more Smart Citation
“…An Figure 1 reports SEM images depicting the surface of the two samples implanted with 5x10 15 at/cm 2 fluence at room and liquid nitrogen temperature, respectively. It is evident that nano-voids formed under Sn + irradiation as expected from literature for high fluencies and high mass ion bombardment [10,11]. The voids are distributed on the sample surface with the typical 'honeycomb' symmetry.…”
Section: Methodssupporting
confidence: 56%
“…In fact, the low diffusivity of Sn in Ge [7,8] and the low temperature SPER [9] would enable the formation of thin Ge 1-x Sn x layers with limited thermal budget. However, ion implantation of high mass species on Ge is known to induce a characteristic "honeycomb" damage structure, impossible to anneal out with conventional thermal treatments [10,11]. Ion implantation was thus carried out at liquid nitrogen temperature to avoid the void formation [12].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown, however, that achieving Sn concentrations in Ge higher than about 6 at:% through ion implantation is severely hindered by a high sputtering effect in Ge and the onset of ionimplantation induced porosity once the Ge is rendered amorphous (a-Ge). 18 It has previously been found that irradiation-induced porosity is favoured in the range of implant temperatures between $ À 80 C and $200 C. [19][20][21] The onset of porosity can be suppressed by undertaking implants outside of this unfavourable temperature window. At elevated temperatures above 200 C, the Ge substrate remains crystalline due to the recombination of mobile vacancies and interstitials.…”
mentioning
confidence: 99%
“…It has been suggested that there is a barrier to point defect recombination at the Ge surface which has been shown to spur the formation of a nanoporous structure. 44,45 In addition, recent reports have noted the Ge surface as acting as a sink for vacancies while reflecting interstitials. 38,39 With increasing B þ implant energy, it has been observed that the active fraction increases with indicates the surface proximity may be affecting the activation behavior.…”
mentioning
confidence: 99%